Enhancement in thermal stability and surface properties of LiFePO4/VFLG composite prepared via sol-gel route - Amri, Amun; Bertilsya Hendri, Yola; Sunarno; Dwi Setyo Pambudi, Yoyok; Assylzhan, Mazhibayev; Elmira, Kambarova; Ain, Khusnul; Jumbri, Khairulazhar; Tao Jiang, Zhong; Yang, Chun-Chen (Communications in Science and Technology, 2025)
Thermal and surface properties of LiFePO4/very-few-layer graphene (LiFePO4/VFLG) composite manufactured through the sol-gel route have been researched for lithium-ion battery cathode application. VFLG was acquired from a facile, cost-effective, and environmentally benign fluid dynamic shear exfoliation process. The composites were characterized through thermogravimetry analysis (TGA), differential scanning calorimetry (DSC), field-emission scanning electron microscopy (FESEM) interlinked with energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), and Braneur-Emmett-Teller (BET) analysis. The TGA-DSC results showed that the integration of VFLG could enhance the thermal stability of the composite by inhibiting oxygen diffusion on the LiFePO4 surface. FESEM-EDX analysis, meanwhile, confirmed the homogeneously distributed VFLG in the composites. TEM results revealed that the average particle sizes of the composites decreased by about 21.2% compared to the bare LiFePO4. TEM and HRTEM results confirmed an intimate contact between VFLG intimately and LiFePO4 particles via plane-to-point contact, contributing to the control and reduction of particle size. Furthermore, physisorption via BET analysis revealed that incorporating VFLG provided a wider distribution of mesopores and increased pore diameter and pore volume by 128.7% and 656.3%, respectively, compared to sole LiFePO4. These significant improvements were related to the flexibility and ability of a thin layer of VFLG to limit the growth of LiFePO4 particles. This approach offers a promising strategy to enhance the thermal stability and surface properties of lithium-ion battery cathodes.